Predictive accuracy of risk scales following self-harm: multicentre, prospective cohort study. - Quinlivan, L; Cooper, J; Meehan, D; Longson, D; Potokar, J; Hulme, T; Marsden, J; Brand, F; Lange, K; Riseborough, E; Page, L; Metcalfe, C; et al. (Royal College of Psychiatrists, 2017)
Background Scales are widely used in psychiatric assessments following self-harm. Robust evidence from prospective diagnostic accuracy cohort studies is lacking. Aims To evaluate the performance of risk scales (Manchester Self-Harm Rule, ReACT Self-Harm Rule, SAD PERSONS Scale, Modified SAD PERSONS Scale, Barratt Impulsivity Scale); and patient and clinician estimates of risk in identifying patients who repeat self-harm within six months. Method A multisite prospective cohort study was conducted of adults aged 18 years and over referred to liaison psychiatry services following self-harm. Scale a priori cut-offs were evaluated using diagnostic accuracy statistics. Area under the curve (AUC) was used to determine optimal cut-offs and compare global accuracy. Results 483 episodes of self-harm were included in the study. There was a repeat episode in 145 of these (30%) within six months. Sensitivity ranged from 1% (95% CI: 0%, 5%) for the SAD PERSONS scale, to 97% (95% CI: 93%, 99%) for the Manchester Self-Harm Rule. Positive predictive values ranged from 13% (95% CI: 2%, 47%) for the Modified SAD PERSONS Scale to 47% (95% CI: 41%, 53%) for the clinician assessment of risk. Area under the curve ranged from 0.55 (95% CI: 0.50, 0.61) for the SAD PERSONS Scale to 0.74 (95% CI: 0.69, 0.79) for the clinician scale. The remaining scales performed significantly worse than clinician and patient estimates of risk (p<0.001). Conclusion Risk scales following self-harm have limited clinical utility and may waste valuable resources. Most scales performed no better than clinician or patient ratings of risk. Some performed considerably worse. Positive predictive values were modest. In line with national guidelines, risk scales should not be used to determine patient management or predict self-harm.